2009
DOI: 10.2214/ajr.07.3727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Intramuscular Cysts in the Rotator Cuff and Their Relationship to Full- and Partial-Thickness Rotator Cuff Tears

Abstract: Our study echoes the findings of previous studies that suggest a relationship between intramuscular cysts and full- and partial-thickness rotator cuff tears but illustrates that the incidence of an isolated intramuscular cyst is higher than previously expected. When intramuscular cysts present with rotator cuff tears, they present with full- and partial-thickness rotator cuff tears in relatively equal proportions. The presence of an intramuscular cyst on MRI, although it may be an isolated finding, should prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…On MRI, possible features of external impingement are a large amount of fluid within the subacromial bursa and medial to the acromioclavicular joint [9], a reduction in the acromiohumeral distance [10], the presence of downward facing acromioclavicular joint osteophytes [11], the shape of the acromion [12] [13] [14], an os acromiale [15] and rotator cuff lesions [16] [17]. However, many of the above lesions have been found in asymptomatic shoulders making radiological diagnosis unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, possible features of external impingement are a large amount of fluid within the subacromial bursa and medial to the acromioclavicular joint [9], a reduction in the acromiohumeral distance [10], the presence of downward facing acromioclavicular joint osteophytes [11], the shape of the acromion [12] [13] [14], an os acromiale [15] and rotator cuff lesions [16] [17]. However, many of the above lesions have been found in asymptomatic shoulders making radiological diagnosis unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Paralabral cysts occur in 2% to 3% of symptomatic shoulders. 7,8 They are located mostly medial to the glenoid rim, lying in the supraspinatus or infraspinatus fossa, and can enlarge around the supraglenoid and spinoglenoid notch. They are often asymptomatic but can be associated with rotator cuff tears 7 or glenoid labral tears.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular rotator cuff cysts have been well characterised and found to be associated with rotator cuff disease. 7 This report describes the very unusual occurrence of a cyst within the supraspinatus tendon itself, causing shoulder impingement. Intratendinous supraspinatus cysts have not been described before.…”
Section: Introductionmentioning
confidence: 93%
“…29 Manval et al demonstrated that intramuscular cysts can be seen in equal proportions with full-thickness or partial-thickness rotator cuff tears. 30 Because these cysts are typically small and located within the muscle, they are not seen during surgery or arthroscopy, and are not palpable on physical examination. The cysts may occur within the muscle of the torn tendon (►Fig.…”
Section: Periarticular Cysts Intramuscular Cystmentioning
confidence: 99%